Assessing the Direct and Indirect Effects of Legitimacy on Public Empowerment of Police: A Study of Public Support for Police Militarization in America. Issue 1 (28th December 2018) - Moule, Richard K.; Burruss, George W.; Parry, Megan M.; Fox, Bryanna
Abstract : The process‐based model dominates contemporary American research on police‐community relations and perceptions of police. A sizable literature has examined the linkages between procedural justice, legitimacy, compliance with the law, and cooperation with police. Less examined is the relationship between legitimacy and public empowerment of police. This study examines this relationship, focusing on police militarization. We first examine the direct effect of legitimacy on public willingness to allow police to become more militarized. Drawing from cognitive psychology and rational choice theories, we then consider indirect paths between legitimacy and empowerment, concentrating on two anticipated consequences of militarization—an increase in police effectiveness and possible harm to civil liberties. Using a national sample of over 700 American adults, and structural equation modeling, results indicate legitimacy has both direct and indirect effects on police empowerment, in part by shaping assessments of the possible consequences of empowerment. Implications for theory and policy are discussed.